CXCR4 antagonism ameliorates leukocyte abnormalities in a preclinical model of WHIM syndrome - Roland, Lilian; Nguyen, Chi Huu; Zmajkovicova, Katarina; Khamyath, Mélanie; Kalogeraki, Maria; Schell, Bérénice; Gourhand, Vanessa; Rondeau, Vincent; Abou Nader, Zeina; Monticelli, Halenya; Maierhofer, Barbara; Johnson, Robert; et al. (Frontiers in Immunology, 2024)
BackgroundWHIM (Warts, Hypogammaglobulinemia, Infections, and Myelokathexis) syndrome is an ultra-rare, combined primary immunodeficiency and chronic neutropenic disorder characterized by a range of clinical presentations, including peripheral neutropenia, lymphopenia, and recurrent infections. WHIM syndrome is most often caused by gain-of-function mutations in the gene encoding C-X-C chemokine receptor 4 (CXCR4). As such, inhibition of CXCR4 with XOLREMDI® (mavorixafor), an orally bioavailable CXCR4 antagonist, demonstrated clinically meaningful increases in absolute neutrophil and lymphocyte counts and concomitant reduction in infections in patients with WHIM syndrome, resulting in its recent U.S. Food and Drug Administration approval. The impact of CXCR4 antagonism on other aspects of the pathobiology in WHIM syndrome, such as lymphopoiesis and leukocyte trafficking between primary and secondary lymphoid organs, is less understood.MethodsIn the current study, the effects of CXCR4 antagonism on leukocyte trafficking and distribution in primary and secondary lymphoid organs were investigated in a mouse model of WHIM syndrome carrying the heterozygous Cxcr41013 mutation. Cxcr4+/1013 and Cxcr4 wild-type mice received the orally bioavailable CXCR4 antagonist X4-185. Blood, spleen and bone marrow samples were collected for numeration, flow cytometry, and functional studies.ResultsCxcr4+/1013 mice exhibited profound peripheral blood leukopenia as seen in patients with WHIM syndrome. CXCR4 antagonism corrected circulating leukopenia and mobilized functional neutrophils without disrupting granulopoiesis in the bone marrow of Cxcr4+/1013 mice. Furthermore, Cxcr4+/1013 displayed aberrant splenic T and B-cell counts and frequency. Treatment with X4-185 normalized splenic T-cell abnormalities, correcting the reduced CD8+ T-cell numbers, restoring the CD4/CD8 T-cell ratio, and ameliorating peripheral blood T-cell lymphopenia. In addition, CXCR4 antagonism was able to correct the abnormal frequencies and numbers of splenic marginal zone and follicular B cells in Cxcr4+/1013 mice, and ultimately normalize B-cell lymphopenia in the peripheral circulation.ConclusionsOur study provides comprehensive evidence that oral dosing with a CXCR4 antagonist can effectively correct WHIM-associated neutrophil and lymphocyte abnormalities in a mouse model of WHIM syndrome. These findings extend our understanding of how targeting the dysregulated CXCR4 signaling pathway can ameliorate the pathogenesis of WHIM syndrome.